FROM THE PALACE PENDOPO TO THE PESANTREN ROOMS:: The Dynamics of Aristocrats and Kiai Relationship in Sumenep (1750-1950s) - Aufannuha Ihsani (Islamuna: Jurnal Studi Islam, 2021)
This article discusses the dynamics of the relation between the sentana (aristocrats) and kèaè (ulama) in Sumenep during the colonial period. The topic is chosen because almost all research put the aristocrats and the ulama in Madura as historically opposed parties. The main question of the article is that how the relationship started and how far it had manifested until the early days of the independence. Collecting data from babad, manuscript, official reports from the colonial government and some informants who are the descendants of the aristocrats, this research applies a social-cultural approach to explain why their close relation with the kèaè have allowed the aristocrats to maintain their dignity in society. The result shows that the close relation between sentana and kèaè originated from the figure of Bindara Saod. Although it had been tenuous because the palace customs have made the aristocrats exclusive, the relationship between sentana and kèaè did not really break. A marriage between the Sultan Abdurrahman’s granddaughter and a kèaè in the mid-19th century tightened the relationship, descending a generation of ulama with royal blood and manifested in a pesantren (Islamic boarding school) in which the palace customs have been kept alive and survived until postcolonial era. [Artikel ini membicarakan dinamika hubungan yang terjalin antara kalangan sentana (bangsawan) dan kèaè (kiai) di Sumenep selama masa kolonial. Topik ini dipilih sebab hampir semua penelitian menempatkan bangsawan dan kiai di Madura sebagai pihak yang bertentangan secara historis. Pertanyaan utama dari penelitian ini adalah bagaimana hubungan itu bermula dan sejauh mana ia terejawantahkan hingga masa-masa awal kemerdekaan. Mengambil data dari babad, manuskrip, laporan-laporan resmi pemerintah kolonial, dan para informan yang merupakan keturunan kaum ningrat, penelitian ini akan menggunakan pendekatan sosio-kultural untuk menjelaskan mengapa kedekatan dengan kèaè membuat para bangsawan dapat menjaga muruah mereka di tengah-tengah masyarakat. Hasil penelitian menunjukkan bahwa kedekatan antara kèaè dan sentana bermula dari sosok Bindara Saod. Kendati sempat merenggang sebab adat keraton mengeksklusifkan kalangan ningrat, jalinan sentana dan kèaè tidak benar-benar putus. Sebuah pernikahan antara cucu Sultan Abdurrahman dan seorang kèaè pada pertengahan abad ke-19 M. mempererat kembali hubungan itu, menurunkan generasi para kiai berdarah biru, dan mewujud dalam sebuah pesantren di mana adat dan budaya keraton tetap hidup dan bertahan hingga era pascakolonial]